SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN KUALITAS STASIUN TELEVISI SEBAGAI KONSUMSI TERBAIK BAGI MASYARAKAT DENGAN MENGGUNAKAN METODE AHP - Raja Tama Andriagus (Universitas Asahan, 2017)
Abstract - A television station is a technology or communication media that displays both audio and visual broadcasts, both black and full color. The number of television stations currently makes fierce competition between television stations to innovate in making broadcasts that attract public attention to get highest rating But often because they want to pursue a rating, many television stations are less concerned about the quality of the broadcasts they display. Decision support system is a system that can be used as a tool to determine station quality television in displaying the broadcast. Data analysis is done by comparing television stations in Indonesia, namely the assessment is taken based on the level of educative, innovative, and human resources (television crew) contained in each television station. The results of the AHP method analysis are helpful conclusions people to know the best television stations as public consumption which tends to need information, knowledge and entertainment. Keywords - AHP, Television Station, Decision Support System